해외기술도입 전략이 기업 성과에 미치는 영향: 한국기업을 중심으로 - 강성룡; 이성주; 김재훈 (대한산업공학회지, 2022)
As the complexity of technology and the convergence between technologies increases, firms have actively utilized foreign technology acquisition to strengthen their competitiveness. Based on TBP(Technology Balance of Payment) data of 243 Korean firms, this paper empirically explores the impact of foreign technology acquisition strategies on the financial performance and the moderating effect of a firm's absorption capacity on the relationship between foreign technology acquisition and firm performance. The results indicate that the scale of foreign technology acquisition has a positive impact on firm performance, while the concentration of technology sources has a negative impact on firm performance. The introduction of intellectual property rights had a negative impact on firm performance but was not statistically significant. This study is expected to provide various implications for firm strategy and technology policy by suggesting the mechanisms for the impact of foreign technology acquisition on firm performance.
Keywords: Foreign Technology Acquisition; Performance; Absorptive Capacity; Technology Balance of Payment